كتاب اللغة العربية للصف الأول في المدارس الإبتدائية الوطنية :bدراسة تقويمية /cإعداد، نئ مرشدة بنت نئ دين - Nik Murshidah Nik Din (Kulliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 2009)
This study evaluates the suitability of the Arabic textbook used for standard one students in National Primary School in Malaysia. This research examined the aspect of languages, cultural, educational and pedagogical contents and some suggestions are proposed towards the improvement of learning textbook. Evaluation tools suggested by Rusydi Ahmad Tu'aymah are implied with modifications to some of its elements to suit the needs of the research in evaluating the textbook. The researcher distributes the evaluation tools among teachers of various national primary schools in Kota Bharu, Kelantan. Based on the teachers' views and observations, the thesis concluded that the contents of the books are suitable for the beginner students (Arabic as a Second Language). Nevertheless, some improvements are still need to be considered by integrating the vocabularies used in the syllabus and the order of the contents without ignoring the Arabic Islamic cultural mixing with local culture. Apart from that, the textbooks should be guided in line with the objectives of j-QAF programme as well as previous beneficial textbooks to ensure the smoothness of constructing a proper textbook.